Supply chain management: Motorola’s complexity index - Khan, Omera (Henry Stewart Talks, 2018)
This case study examines the success of Motorola’s complexity index in reducing complexity across its supply-chains. At Motorola, competitive pressures caused the company to increase its product variation, making it difficult to closely match demand. However, by focussing on complexity reduction, Motorola was able to significantly reduce costs and improve company responsiveness.